Anthrenus (Anthrenus) mumbaiensis sp. nov. from India and a morphometric examination of Anthrenus (Anthrenus) festivus (Coleoptera, Dermestidae, Anthrenini) - Holloway, Graham J. (Zootaxa, 2023)
All examples of Anthrenus (Anthrenus) festivus were borrowed from the Natural History Museum, London for dissection to provide good images of external and internal features. Images of habitus, ventrites and antennae are presented along with aedeagus and sternite IX. The purpose of this was to provide clear information for future comparative taxonomic studies. During the examination of the specimens, a new species was discovered that had been collected in Bombay (Mumbai) in the late 19th century. Images of external and internal features of the holotype (male) and paratype (female) are provided. The new species is named Anthrenus (Anthrenus) mumbaiensis after the location of collection. Collection data from the study specimens, Andreas Herrmann’s private collection, the literature, and verifiable images on iNaturalist were used to generate a distribution map. The map showed that A. festivus is found mainly in coastal regions of the western Mediterranean.